Modeling of uranium trioxide to uranium tetrafluoride conversion using a moving bed reactor. - Silva, Gabriel Migliano (2021)
In order to comply with the National Defense Strategy, the Marinha do Brasil is currently developing a project for the construction of nuclear-driven submarines, which uses enriched uranium oxide pellets as fuel. One of the manufacturing steps for this chemical compound is the conversion of uranium trioxide to uranium tetrafluoride using hydrogen fluoride, which occurs in a moving bed reactor, also called a furnace. Motivated by the scarcity of studies in the literature and the need presented by the Marinha do Brasil, this work aims to develop a model for the conversion of UO3 into UF4 in a moving bed reactor using MATLAB® software. This model utilizes a set of partial differential equations and boundary conditions obtained from the literature, as well as the reactor geometry from the Marinha do Brasil project, which is then solved using a Newton method from the software subroutines. Results, such as solids densities, gas concentrations, temperature and pressure plots, are obtained and discussed herein, showing compatibility to the literature.